2010
DOI: 10.1017/s1368980010001758
|View full text |Cite
|
Sign up to set email alerts
|

Association between socio-economic status and childhood undernutrition in Bangladesh; a comparison of possession score and poverty index

Abstract: Objective: To determine how much of the variation in nutritional status of Bangladeshi children under 5 years old can be attributed to the socio-economic status of the family. Design: Nutritional status used reference Z-scores of weight-for-age (WAZ), height-for-age (HAZ) and weight-for-height (WHZ). A 'possession score' was generated based on ownership of a radio, television, bicycle, motorcycle and telephone, and the availability of electricity, with categories of 0 to 41 possessions. A five-point (quintile)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
42
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 9 publications
(14 reference statements)
8
42
0
1
Order By: Relevance
“…The possession variable was then categorized into five categories of 0 to 4, where 0 means the household had no assets and 4 means that family had all four assets. The 'possession score' was used because a previous study in Bangladesh indicated that this score provided much greater discrimination of undernutrition than a wealth index generated by the principal component analysis technique (15) . All continuous data were checked for skewness using the Cox test (coefficient of skewness divided by the standard error of skewness) as well as examination of the frequency distribution with a normal curve.…”
Section: Methodsmentioning
confidence: 99%
“…The possession variable was then categorized into five categories of 0 to 4, where 0 means the household had no assets and 4 means that family had all four assets. The 'possession score' was used because a previous study in Bangladesh indicated that this score provided much greater discrimination of undernutrition than a wealth index generated by the principal component analysis technique (15) . All continuous data were checked for skewness using the Cox test (coefficient of skewness divided by the standard error of skewness) as well as examination of the frequency distribution with a normal curve.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of relative poverty on gender inequalities in undernutrition was examined by partitioning the sample according to the household possession score; a measure of household socio-economic status that has been previously validated as a predictor of child undernutrition in Bangladesh (Mohsena et al, 2010). The results showed no gender inequalities in health across the different possession score groups, and a similar level of nutritional status across all possession score groups.…”
Section: Discussionmentioning
confidence: 99%
“…A possession index was calculated based upon responses to the questionnaire about household ownership of electricity; a motorcycle; radio or television. This followed a previously validated possession score (Mohsena et al, 2010) except that the present study asked about the possession of a motorcycle whereas Mohsena et al, (2010) included the possession of a bicycle. This possession score has been shown to be a better predictor of undernutrition among under 5 year old children in Bangladesh than the poverty index (Mohsena et al, 2010).…”
Section: Background and Methodsmentioning
confidence: 99%
“…These factors may vary substantially across and within countries and impact on learning in more than one way. In many developing nations, low SES correlates with poor nutritional status (Adeladza 2009;Mohsena et al 2010), which can have a fundamental impact on brain development and learning (Dani et al 2005; and see Tanner and Finn-Stevenson 2002;and Bhargava 2001 for reviews and policy implications in developed and developing nations respectively). Nutrition should therefore be seen not only as fundamental for physical health but also as relevant to educational health.…”
Section: Socioeconomic Statusmentioning
confidence: 99%